Directions for improving the efficiency of human resource management at enterprises of the fuel and energy complex ("Journal "U". Economy. Management. Finance.", 2022)
Тhe key sector of the domestic economy is the fuel and energy complex, which is subject to significant sanctions pressure. The article deals with modern trends and problems of human resource management. The necessity of applying the current algorithm of socio-psychological adaptation, starting their labor activity in the fuel and energy complex, is substantiated.
Keywords: fuel and energy complex; sanctions; economic development; human resources; personnel management; socio-psychological adaptation